Incorporating neuroendocrine methods into intergroup relations research. (May 2015) - Page-Gould, Elizabeth; Akinola, Modupe
Intergroup researchers have the opportunity to access to a wide variety of methods to help deepen theoretical insights about intergroup relations. In this paper, we focus on neuroendocrine measures, as these physiological measures offer some advantages over traditional measures used in intergroup research, are noninvasive, and are relatively easy to incorporate into existing intergroup paradigms. We begin by discussing the major neuroendocrine systems in the body and their measurable biological products, emphasizing systems that have conceptual relevance to intergroup relations. We then describe how to collect, store, and quantify neuroendocrine measures. Altogether, this paper serves as a primer for intergroup researchers interested in adding neuroendocrine measures to their methodological toolkits to enrich the study of intergroup relations.